Designing an Empowerment Model for Developing Professional and Ethical Competencies of Primary School Managers - Rahimi, Tahereh; Moazzami, Mojtaba; Jahed, Hossein Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The research aims to design an empowerment model for developing professional and ethical competencies in primary school managers.Method: It employs a mixed exploratory (qualitative-quantitative) method, involving selected experts from the education organization for the qualitative part. The sample size was 17, following the saturation principle. The quantitative population included 1500 primary school managers in Tehran, with a sample size of 306 determined using Cochran's formula and random cluster sampling. Data were measured using semi-structured interviews and researcher-made questionnaires. The validity of the questionnaire was confirmed and reliability was calculated using Cronbach's alpha (0.870). Data analysis used Strauss's method for content analysis, the Delphi technique, and structural equation modeling with SPSS22 and AMOS26.Findings: Findings indicated that 75% of primary school managers' professional and ethical competencies relate to empowerment dimensions: Technical, Human, Cognitive, Communicative, Teamwork Skills, Initiative Skills. These can explain and predict competencies comprising Individual Characteristics, Management Skills, Organizational Factors, Entrepreneurial Competence, Business Competence, Leadership, Decision Making, Collaboration.Conclusion: In conclusion, the study successfully designs an empowerment model that significantly contributes to the development of professional and ethical competencies among primary school managers. This model, grounded in comprehensive research and expert insights, demonstrates the vital role of empowerment in enhancing the essential managerial competencies needed for effective educational leadership in primary schools.